Novel CYLD pathogenic variant associated with multiple cylindromas of the scalp-A case report - Inês P. Amaral; Ivânia Soares; Madalena P. Correia; Catarina Correia; Pedro Vasconcelos; Luis S. Almeida; Paulo Filipe (Wiley, 2024)
Abstract Cylindromas are rare, benign adnexal neoplasms primarily found on the scalp and face, with a higher incidence in women and typically manifesting in the second or third decade of life. These tumours can present as single or multiple nodules, with the latter form often linked to CYLD gene mutations, particularly in the context of CYLD cutaneous syndrome. Here, we report a case of a 61‐year‐old male presenting with multiple cylindromas of the scalp, prompting genetic testing that revealed a novel pathogenic variant in the CYLD gene.